KOMUNIKASI TERAPEUTIK PERAWAT TERHADAP TINGKAT KECEMASAN KELUARGA PADA PASIEN YANG DI RAWAT DI RUANG PERAWATAN KHUSUS RSUD MM DUNDA LIMBOTO - Sabirin B. Syukur; Rini Asnawati; Putri Indarwati Nusi (Universitas Muhammadiyah Gorontalo, 2020)
This research was carried out at the MM. DundaLimboto Hospital. The purpose was to determine the relationship between communication skil of nurses and the level of anxiety of patient’s family. The design was analityc observational with cros sectional study approach. The samples were 60 samples. The data was analyzed by using a Chi square statistical test. The result showed that there is a significant relationship between communication of nurses and the level of anxiety of patient’s family with p value = 0,00 (<a0,05). Thus Ha was accepted and Ho was rejected.